2005
DOI: 10.1063/1.1944202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phase transformations on laser forming of Ti–6Al–4V alloy

Abstract: Surface deformation behavior of beta solution treated and overaged Ti-6Al-4V during laser shock processingIn laser forming, phase transformations in the heat-affected zone take place under steep thermal cycles, and have a significant effect on the flow behavior of Ti-6Al-4V alloy and the laser-forming process. The flow-stress data of a material are generally provided as only dependent on strain, strain rate, and temperature, while phase transformations are determined by both temperature and temperature history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 21 publications
3
64
0
Order By: Relevance
“…It is known that Ti-6Al-4V is an αþβ alloy and that the volumetric fraction of the α phase, which is about 90% at room temperature (Henry et al, 1995;Facchini et al, 2010), decreases with increasing temperature until it is completely transformed into β phase when the temperature reaches β-transus. According to the literature (Ahmed and Rack, 1998;Vrancken et al, 2012;Pederson et al, 2003;Fan et al, 2005;Veiga et al, 2012), the β-transus temperature of Ti-6Al-4V is about 970750 1C. Based on dilatometric experiments, Homporová et al (2011) reported that the α-β transformation in Ti-6Al-4V alloy with duplex microstructure occurs between 750 and 1050 1C.…”
Section: Resultsmentioning
confidence: 95%
“…It is known that Ti-6Al-4V is an αþβ alloy and that the volumetric fraction of the α phase, which is about 90% at room temperature (Henry et al, 1995;Facchini et al, 2010), decreases with increasing temperature until it is completely transformed into β phase when the temperature reaches β-transus. According to the literature (Ahmed and Rack, 1998;Vrancken et al, 2012;Pederson et al, 2003;Fan et al, 2005;Veiga et al, 2012), the β-transus temperature of Ti-6Al-4V is about 970750 1C. Based on dilatometric experiments, Homporová et al (2011) reported that the α-β transformation in Ti-6Al-4V alloy with duplex microstructure occurs between 750 and 1050 1C.…”
Section: Resultsmentioning
confidence: 95%
“…Only few papers address the topic of the Koistinen-Marburger coefficient, coefkm. Fan et al (2005) evaluated the coefficient to 0.003 after experiments by Malinov et al (2001a). The author of the current thesis evaluated the same parameter from spot weld experiments (Elmer et al 2005b) to be 0.005.…”
Section: Martensite Transformation Parametersmentioning
confidence: 99%
“…Diverse modelling methods are applied to model phase transformations and some of the transformation kinetics associated have been evaluated for titanium alloys [19]. The phase transformation kinetics during either isothermal or cooling processes have been successfully described with the JMAK model , Avrami [26] and Kolmogorov [33]) for titanium alloys [34], especially for Ti-6Al-4V [11,19,35]. Nevertheless, phase transformations during heating have been studied by a few authors [28,36].…”
Section: Materials Modellingmentioning
confidence: 99%
“…Malinov et al [19,20] studied the phase transformation kinetics under isothermal condition using resistivity technique and continuous cooling conditions using differential scanning calorimetry at different cooling rates using the Johnson Mehl Avrami and Kolmogorov (JMAK) equation [21][22][23] and the additivity rule to determine the fraction of β transformed to α. Ahmed and Rack [24] studied the effects of cooling rate from above the beta transus on phase transformation during cooling and determined that martensitic formation forms at high cooling rates above 410 K/s, while Gil Mur et al [25] studied the decomposition of martensite into α and β during tempering heat treatment and observed fully martensitic structure at much lower rates. Kelly and Kampe [26,27], Crespo et al [28] and Murgau et al [29] modelled microstructural evolution in Ti-6Al-4V during a laser metal deposition process and Fan et al [30] numerically investigated the effect of phase transformations on laser forming of Ti-6Al-4V using JMA kinetic parameters for isothermal transformation from Malinov et al [19] but without applying additivity principles to diffusion controlled transformation. Elmer et al [7] measured experimentally using the synchrotron X-ray diffraction technique the transformation kinetics during gas tungsten arc welding (GTAW) of Ti-6Al-4V.…”
Section: Solid State Phase Transformationsmentioning
confidence: 99%